Efeitos do treinamento aeróbio no fator de crescimento endotelial vascular (VEGF), funções cognitivas e funcionalidade motora na Doença de Alzheimer - Vital, Thays Martins [UNESP] (2015)
Recently it has been suggested in the literature that trophic factors could be related to the benefits of physical exercise on mental health of elderly with Alzheimer's disease (AD). Among this factor, in this study, the vascular endothelial growth factor will be highlighted, which makes an important role in neurogenesis and angiogenesis process. This study was divided in five chapters. The first presented the introduction, objectives, study design and review of the literature. The second chapter consisted of a review article aimed to conduct a systematic review of studies that found the effects of exercise on VEGF in the elderly. Already chapter three consisted of an exploratory study and the aim was to compare the plasma concentrations of VEGF, cognitive functions and motor functionality of cognitively preserved elderly and with AD. Another aim of this study was to determine and compare the acute effect of an aerobic exercise session in plasma levels of VEGF both populations. This study was composed of 40 cognitively preserved elderly and 40 elderly in the mild stage of AD. Elderly of both groups performed a protocol assessments consisting of cognitive and motors tests, blood collection to obtain plasma levels of VEGF and metabolic variables (hemogram, total cholesterol and fractions, triglycerides and glucose) and an incremental test. The independent t test showed that the groups were different at baseline for the following variables: level of physical activity, blood glucose and platelets. The statistical testes showed that AD patients have lower VEGF concentrations before and after the incremental test, when compared to the group of cognitively preserved elderly. The group of elderly with AD also has a worse motor functionality.However, an aerobic exercise session does not increase significantly the VEGF levels in both groups. The chapter 4 is a longitudinal study and the aim was to verify the effects of aerobic training in plasma ...